THE ROLE OF WOMEN FARMERS IN RICE FARMING IN EAST LANGSA DISTRICT, LANGSA CITY: PERAN WANITA TANI DALAM USAHATANI PADI SAWAH DI KECAMATAN LANGSA TIMUR KOTA LANGSA - Fitri Amelia Sihaloho; Fiddini Alham; Faoeza Hafiz Saragih (Universitas Widya Gama Mahakam, 2026)
This study aimed to analyze the roles of women farmers in the productive, reproductive, and social aspects of lowland rice farming, their working time allocation, and their income contribution to household income in East Langsa District, Langsa City. The method used in this study was quantitative descriptive analysis. The research location was determined purposefully in three villages with the highest number of farmer households, while the respondents were selected using simple random sampling from the sample farmer households. The data used in this study consisted of primary and secondary data. The data analysis methods used included descriptive percentage analysis, calculation of women farmers’ working time allocation, and calculation of the contribution of women farmers’ income to household income. The results showed that the role of women farmers in lowland rice farming in the productive aspect was most dominant in planting activities, with an involvement rate of 100%, while the lowest involvement was found in land preparation activities, at 0%. In the reproductive and social aspects, women farmers played an active role in household activities and social community activities such as religious gatherings, PKK, and posyandu. The average working time allocation of women farmers for productive or income-earning activities was 59.47% of the total working time allocation, which included productive, reproductive, and social activities. The contribution of income provided by women farmers was 22.37%. This indicates that the income contribution of women farmers in lowland rice farming was included in the medium contribution category (20.01– 30.00%).